Abordagem via integrais de trajetória do processo de troca e dissipação de energia num sistema composto por dois osciladores harmônicos dissipativos acoplados - o modelo duplicado de Caldeira & Leggett - Cacheffo, Alexandre (2005)
In this work, we analyse the dissipation and interchange of energy in a system composed by two harmonic oscillators, each one associated with a thermal reservoir. To this end, we employ the Caldeira & Leggett approach, based on path integral formulation, to obtain the time evolution of the reduced density operator of the system composed by both oscillators.